A critical discussion of how psychological and biological factors influence the development of anxiety disorders. - A. Ganotis; G. Thomas; P Louka (Dialogues in Clinical Neuroscience & Mental Health, 2023)
Anxiety disorders are becoming a common symptom, with the number of people affected by them rapidly multiplying. Numerous studies try to explain their nature, yet there are no clear answer so far as to what exactly causes them. Up to date bibliography on psychological and biological factors possibly correlating with anxiety disorders, with a focus on genes, chromosomes, proteins, HPA axis, serotonin, the environment and even maternal care are critically discussed.